The process of establishing marine spatial planning maps in Vietnam - Tran Duc, Thanh; Dang Hoai, Nhon; Nguyen Van, Thao; Cao Thi, Thu Trang; Vu Duy, Vinh; Duong Thanh, Nghi; Nguyen Dang, Ngai; Nguyen Thi, Kim Anh (Vietnam Journal of Marine Science and Technology, 2023)
Creating a marine spatial planning map (MSP) guides the determination of the map's extent and scale, the map, the content of the map, the methods and techniques of mapping, and the sequence of steps performed. The process consists of 5 steps: 1) Define nature, requirements, scope, and methods, 2) Analyze and evaluate data and information, 3) Make and draw thematic maps and diagrams, 4) MSP mapping, and 5) Make a description of the MSP map. MSP maps' location, scope, and scale are established according to a 3-level system: national, regional, and local. The three-dimensional approach MSP map is integrated and synthesized from the marine functional zoning and marine space use zoning maps of the same scale. The set of MSP maps in Vietnam is divided into 3 levels: national level MSP maps with a scale of 1:1,000,000; regional MSP map, scale 1:500,000 together with MSP map of sub-regions at 1:250,000 scale; local-provincial MSP maps at the scale of 1:100,000 and in case of necessity, establish district-level MSP maps at scale 1:25,000–1:50,000. Vietnam's sea is functionally divided into 5 large marine regions, including the Gulf of Tonkin. The Gulf of Tonkin (region I) is divided into 6 functional zones, including Mong Cai - Do Son one. This area is established MSP Map at scale 1:250,000 as a reference example, showing 3 functional areas and 7 basic units using marine space.